The Influence of the Application of Game Based Learning (GBL) Models Assisted by the Math Games Platform on the Mathematics Learning Outcomes of Fifth Grade Elementary School Students - Rizky Ayu Wachdani; M. Anas Thohir; Yudithia Dian Putra (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study The Influence of the Application of Game Based Learning (GBL) Models Assisted by the Math Games Platform on the Mathematics Learning Outcomes of Fifth Grade Elementary School Student this study uses an experimental quantitative approach to determine whether or not there is a result of a treatment. This study aims to determine the effect of implementing the Game Based Learning (GBL) model with the help of the Math Games platform on the mathematics learning outcomes of fifth grade elementary school students. This study used the One Group Pretest-Posttest Design method, with a subject of 29 students in an elementary school in Kediri Regency which was taken through purposive sampling technique. Data collection techniques using observation and objective tests. The instrument used was a multiple choice test with 10 questions that had been tested to determine the validity and reliability of the instrument. The results were analyzed using descriptive statistics and inferential statistics with the help of SPSS for Windows version 21. Based on the results, the mean pretest score was 60.35 and the posttest average score was 85.52 with an N-gain percentage of 66%. Analysis of research data was carried out through 2 stages, namely prerequisite tests and hypothesis testing. Based on the results of the prerequisite test, it was found that the research data were normal and homogeneous (having the same variance). The results of the hypothesis analysis using the paired sample t-test show that the data significance value is 0.000, where 0.000 0.05, which means Ho is rejected and Ha is accepted. So it can be concluded that there is a significant difference between learning outcomes before and after the implementation of the game based learning model with an average increase in learning outcomes in the medium category.